Quality of Professional Life and Burnout of the Nursing Staff at an Intensive Care Unit in Venezuela - Pedro José Quijada-Martínez; Irmarys Rosangel Cedeño-Idrogo; Guillermo Terán-Ángel (Universidad de Antioquia, 2021)
Objective. To determine the relationship between the level of quality of professional life and the characteristics of the burnout syndrome of the nursing staff in the intensive care unit. Methods. An analytic cross-sectional study was conducted in the intensive care unit of a public hospital in Mérida (Venezuela), with the participation of 40 nurses from a total population of 43. The Professional Quality of Life of 35 items (QoPL-35) and Maslach Burnout Inventory scales were used. Results. Of the participants, 67.5% were professionals and 32.5% were residents, < 41 years of age (75%) and of female sex (90%). The professional quality of life was regular (median = 213), the intrinsic motivation dimension was the best scored (median = 76), followed by that of workload (median = 68) and that of directive support (median = 65). The prevalence of high burnout syndrome was 22.5%; emotional exhaustion affected 75.5% of the participants and 37.5% had low personal achievement. The level of professional quality of life was related with the severity of the burnout syndrome (p=0.04). Conclusion. The professional quality of life of the nurses in the ICU studied was regular and is associated with a higher risk of suffering severe burnout syndrome.